Older persons: the development of legal protection on emotional abuse in domestic violence - Ahmad, Noor 'Aza (Global Academic Excellence, 2018)
Due to life expectancy, the older persons will need to stay together with their family’s members, normally with their adult children or grandchildren or even extended family members. This paper seeks to discuss the provision of the right of the older persons to be protected as regards to emotional or psychological abuse against domestic violence. By the year 2050, Malaysia will be considered as an Aging Nation. In order to cope with the increase in the elderly population, there is a need to have legal protection against domestic violence as to the older person’s psychological and emotional injury. In other words, it is important to ensure that the right, in particular, the aging citizens or older person regards, on emotional abuse in domestic violence.